2011
DOI: 10.1029/2010sw000647
|View full text |Cite
|
Sign up to set email alerts
|

An improved forecast system for relativistic electrons at geosynchronous orbit

Abstract: Here we provide a review of existing forecast models for Earth's outer radiation belt electrons, discuss some recent improvements to two of these models, and present a new and improved forecast system for relativistic electrons at GEO. For the first time, we can forecast at a local hour resolution around GEO using a statistical tool included in the system. This forecast system also includes several real‐time forecast models, two previously existing and one that is a new development. This new model incorporates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 50 publications
0
21
1
Order By: Relevance
“…The declining phase and minimum of solar cycle 23 provide an independent test of the model. This model has also been revised to make real‐time forecasts one and two days ahead of >2 MeV electron fluxes at GEO using real‐time solar wind data from ACE, normalized with real‐time GOES measurements at GEO [e.g., Li , 2004; Turner and Li , 2008; Turner et al , 2011].…”
Section: Introductionmentioning
confidence: 99%
“…The declining phase and minimum of solar cycle 23 provide an independent test of the model. This model has also been revised to make real‐time forecasts one and two days ahead of >2 MeV electron fluxes at GEO using real‐time solar wind data from ACE, normalized with real‐time GOES measurements at GEO [e.g., Li , 2004; Turner and Li , 2008; Turner et al , 2011].…”
Section: Introductionmentioning
confidence: 99%
“…In the upper panel it can also be seen that the flux decay is reproduced by the model. (Turner et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, as these models are based on averages taken over large timescales, they fade away the characteristics of physical processes that drive the dynamic of particle flux variations. Recently, space weather preoccupations have therefore encouraged the development of dynamic models, either physics based (Beutier & Boscher 1995;Fung 1996;Glauert & Horne 2005;Koller et al 2007;Fok et al 2008;Albert et al 2009;Subbotin & Shprits 2009) or empirical (O'Brien & McPherron 2003;Ling et al 2010;Turner et al 2011). The physics-based models are mostly data-driven physical models that incorporate a radial diffusion code and where the measured data provide the boundary conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They note that the worst forecasts occurred during solar maximum (second half of 1999 through first half of 2002), better forecasts during the declining years of solar minimum (second half of 2002 through 2008), and their best forecasts during the inclining years of solar minimum (1996 through first half of 1999). Turner et al [] reviewed forecasting models for Earth's outer radiation belt electrons other than those considered by Perry et al [] but come to similar conclusions, namely that forecast accuracy is related to the solar cycle. Kellerman et al [] examined forecast accuracy for their geosynchronous radiation belt electron empirical prediction model between 1991 and 2009.…”
Section: Parameter Estimate Sensitivity To Training Datamentioning
confidence: 98%
“…By fitting Model separately for each year, we are able to detect that parameter estimates change over time. The time‐varying functional relationship between log electron flux and solar wind speed has been noted in the literature [e.g., Reeves et al , ; Perry et al , ; Turner et al , ; Kellerman et al , ]. Reeves et al [] graphically examined the long‐term variations between solar wind speed and log electron flux and concluded that the functional relationship between these two variables is not constant in time.…”
Section: Parameter Estimate Sensitivity To Training Datamentioning
confidence: 99%